2022
DOI: 10.3390/ijms23042284
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Membrane Receptors for Sex Steroids Are Involved in the Regulation of Delta/Serrate/LAG-2 Proteins in Rodent Sertoli Cells

Abstract: Delta/Serrate/LAG-2 (DSL) proteins, which serve as ligands for Notch receptors, mediate direct cell–cell interactions involved in the determination of cell fate and functioning. The present study aimed to explore the role of androgens and estrogens, and their receptors in the regulation of DSL proteins in Sertoli cells. To this end, primary rat Sertoli cells and TM4 Sertoli cell line were treated with either testosterone or 17β-estradiol and antagonists of their receptors. To confirm the role of particular rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The ZIP9 has been described as a membrane androgen receptor ( 19 , 20 , 26 , 28 , 46 , 48 , 73 75 ). Thomas et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ZIP9 has been described as a membrane androgen receptor ( 19 , 20 , 26 , 28 , 46 , 48 , 73 75 ). Thomas et al.…”
Section: Discussionmentioning
confidence: 99%
“…The ZIP9 has been described as a membrane androgen receptor (19,20,26,28,46,48,(73)(74)(75). Thomas et al (24) found ZIP9 in the perinuclear and plasma membrane of MDA-MB-468 cells, while some studies also detected it in the reverse Golgi network (76).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, that the classic AR is anchored to the plasma membrane; second, that a still unknown AR exists; and third, that mAR is a splice variant of the classic AR (Garza‐Contreras et al, 2017). In Sertoli cells, the membrane androgen receptor ZRT‐ and Irt‐like protein 9 (ZIP9) have been discovered (Lustofin et al, 2022). AR45, a 45 KDa mAR, a variant of the mAR is localized to lipid rafts in the plasma membrane of the neurons (Fadeyibi et al, 2022).…”
Section: Androgensmentioning
confidence: 99%
“…These different ARs allow to differentiate genomic and nongenomic androgen actions respectively. Both, nuclear and membrane receptors are expressed in the same cell (Lustofin et al, 2022).…”
Section: Androgensmentioning
confidence: 99%